Implementation of a Community-Based Public Model for the Prevention and Control of Communicable Diseases in Migrant Communities in Catalonia - Jordi Gómez i Prat; Helena Martínez Alguacil; Sandra Pequeño Saco; Hakima Ouaarab Essadek; Jordi Montero i Garcia; Oriol Catasús i Llena; Jacobo Mendioroz Peña (Tropical Medicine and Infectious Disease, 2023)
In high-income countries, migrant populations have a greater epidemiological vulnerability: increased exposure to infectious diseases, difficulties in diagnosis, case follow-up and contact tracing, and obstacles following preventive measures related to cultural and administrative barriers. This study aims to describe the implementation of a community-based program to address these challenges. The target population is the migrant native population from North Africa, South Asia, Sub-Saharan Africa, Eastern Europe, and Latin America resident in Catalonia during 2023. Implementation phases include the identification of the perceived needs, search, recruitment and capacity building of 16 community health workers, and the development of a computer software. From January to June 2023, 117 community-based interventions have been implemented, reaching 677 people: 73 community case and contacts management interventions, 17 community in-situ screenings (reaching 247 people) and 27 culturally adapted health awareness and education actions (reaching 358 people). The program addresses the following infectious diseases: tuberculosis, Chagas disease, hepatitis C, typhoid, scabies, hepatitis B, mumps and tinea capitis. The implementation of a community-based model may be key to improving surveillance communicable diseases, promoting an equitable and comprehensive epidemiological surveillance system.